Crop production and farm incomes in two areas of the central dry zone: Findings from June 2021 - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Using data from six phone survey rounds between June 2020 and June 2021, we found that the impacts of the recent political unrest in Myanmar further compound the disruptions caused by the COVID-19 pandemic, both on the farm as well as on the non-farm rural economy.